1992
DOI: 10.1111/j.1469-8137.1992.tb01805.x
|View full text |Cite
|
Sign up to set email alerts
|

Water stress effects on successional populations of the dioecious herb, Rumex acetosella L.

Abstract: The effects of water stress and rewatering on the water relations and biomass of male and female plants of the dioecious herb, Rumex acetosella L., have been examined. Plants were collected from two fields, 2 and 15 yr old respectively, and submitted to different water regimes. Male plants from both populations showed a similar response to water deficit, having a low transpiration rate and low consumption of soil water, whilst maintaining a high green leaf area. Females from the two populations differed from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…The ability of the late-season Chrysopogon to reduce the water loss from its tissues is well documented by Noitsakis & Nastis (1985), who found that this species maintains high turgor potential because of the rigidity (high elasticity module) of the cell wall. The mid-season species Rumex also responds to water deficit by restricting water loss and maintaining higher values of RWC a behaviour which resembles the C plants (Houssard et al, 1992). Because leaf water potential is positively related to soil matric potential, the earlyseason species are thought to be more sensitive to water deficit.…”
Section: Discussionmentioning
confidence: 98%
“…The ability of the late-season Chrysopogon to reduce the water loss from its tissues is well documented by Noitsakis & Nastis (1985), who found that this species maintains high turgor potential because of the rigidity (high elasticity module) of the cell wall. The mid-season species Rumex also responds to water deficit by restricting water loss and maintaining higher values of RWC a behaviour which resembles the C plants (Houssard et al, 1992). Because leaf water potential is positively related to soil matric potential, the earlyseason species are thought to be more sensitive to water deficit.…”
Section: Discussionmentioning
confidence: 98%
“…In a review of the literature I found relevant information on 47 species, including a quantification of the amount of biomass invested in reproduction per reproductive bout by both sexes for 29 species (Table l). For a further four species, Chamaedorea bartingiana, Ilex montana, Nyssa aquatica, and Phoradendron tomentosum, information Dawson et al, (1990) juniperinum Phoradendron P>M P>M P>M Nixon and Todzia (1985) tomentosum Rhamnus Guitian (1995) alaternus Rubus Agren (1987Agren ( , 1988 chamaemorus Rumex acetosa Putwain and Harper (1972); Korpelainen (1991Korpelainen ( ,1992 Korpelainen (1991Korpelainen ( , 1992; Houssard et al (1992Houssard et al ( , 1994 Alliende and Harper (1989) a Growth rate differs depending on soil moisture, with females growing more than males in streamside populations and males more in nonstreamside populations . Note that sex ratio also varies along with soil moisture.…”
Section: Patterns Of Sexual Dimorphism In Life-history Traitsmentioning
confidence: 99%
“…Soil moisture level of 60% reduced both photosynthetic rate and leaf conductance in both males and females. Houssard et al (1992) reported a differential response to moisture stress in male and female plants collected from 2-and 15-year-old successional sites. Males from both sites had reduced transpiration and water consumption rates under drought conditions.…”
Section: Growth and Developmentmentioning
confidence: 97%
“…The ability to reproduce from creeping roots and its long-lived soil seed bank allows this species to easily withstand fire disturbance (Esser 1995). The well-developed root system also offers protection from drought; male individuals are typically more drought tolerant than females, which is likely due to the increased allocation of resources to vegetative growth in males (Zimmerman and Lechowicz 1982;Houssard et al 1992;Fujitaka and Sakai 2007). The low growth profile of the basal rosette of R. acetosella provides the plant with some protection from mowing or grazing (Anonymous 2006).…”
Section: Growth and Developmentmentioning
confidence: 98%
See 1 more Smart Citation